2022
DOI: 10.3390/app122010419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spray Application of Lactic Acid Solution and Aromatic Vinegar on the Microbial Loads of Wild Boar Carcasses Obtained under Optimal Harvest Conditions

Abstract: Solutions of lactic acid 2% and aromatic vinegar were investigated for microbial load reduction on the surfaces of wild boar carcasses. The animals were hunted and processed according to production specifications to obtain the best hygiene for carcasses. The solutions were sprayed on carcass surfaces after skinning, and sites of 5 × 5 cm were sampled 2 h and 48 h post-treatment, with the carcasses under refrigeration conditions. The values of the microbial loads were lower for lactic-acid-treated sites, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This study confirmed both in vitro and in situ that Gram-positive bacteria are more sensitive to polyphenolic compounds compared to Gram-negative bacteria, as widely highlighted in the literature (Seow et al, 2014;Fasolato et al, 2015;Oulahal and Degraeve, 2022). Several compounds, such as weak acids, phenols, and essential oils, have been studied to evaluate their ability to reduce the microbial load of carcasses (Dakheli, 2020;Gonzalez-Fandos et al, 2020;Sallam et al, 2020;Kannan et al, 2021;Roila et al, 2022). Due to their potential bacteriostatic capacity to slow down and delay the growth of L. monocytogenes, olive mill wastewater polyphenolic extracts might be applied to carcasses as a preventive approach to reduce surface contamination and microbial growth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study confirmed both in vitro and in situ that Gram-positive bacteria are more sensitive to polyphenolic compounds compared to Gram-negative bacteria, as widely highlighted in the literature (Seow et al, 2014;Fasolato et al, 2015;Oulahal and Degraeve, 2022). Several compounds, such as weak acids, phenols, and essential oils, have been studied to evaluate their ability to reduce the microbial load of carcasses (Dakheli, 2020;Gonzalez-Fandos et al, 2020;Sallam et al, 2020;Kannan et al, 2021;Roila et al, 2022). Due to their potential bacteriostatic capacity to slow down and delay the growth of L. monocytogenes, olive mill wastewater polyphenolic extracts might be applied to carcasses as a preventive approach to reduce surface contamination and microbial growth.…”
Section: Discussionsupporting
confidence: 83%
“…Regardless, its use should not be considered a substitute for good hygienic practices during slaughtering procedures (EFSA, 2011). Several authors have highlighted the potential of various substances and compounds to limit microbial development (Dakheli, 2020;Gonzalez-Fandos et al, 2020;Han et al, 2020;Roila et al, 2022). Olive oil industry by-products are regarded as a source of bioactive molecules such as polyphenols that, due to their antimicrobial and antioxidant capacity (Foti et al, 2021), might be used to treat carcasses to enhance hygienic and quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…The level of bacterial contamination is very important for fresh meat as it could affect its quality. The growth of spoilage microorganisms, together with endogenous enzymes and oxidation, can degrade various nutrients in meat and generate off-odors and off-flavors, as well as discoloration and slime, making the meat unfit for human consumption and generating waste [ 36 ]. For these reasons, the chemical antimicrobial treatment of hunted game carcasses, such as with lactic acid, has been suggested by different authors to be able to prevent bacterial growth during storage [ 32 , 37 ].…”
Section: Introductionmentioning
confidence: 99%